2012
DOI: 10.1155/2012/726415
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Air Annealing and Gamma Ray Irradiation on the Optical Properties of Cl16FePc Thin Films

Abstract: Metal phthalocyanines are one of the most promising candidates to be used in the fabrication of such devices. Among various phthalocyanines, Iron Hexadecachloro Phthalocyanine (Cl16FePc) has received less attention. Basic characteristics of Cl16FePc are not reported in literature. Hexadecacholoro phthalocyanines have attracted interest as possible n-type organic semiconductor with high electron mobility and good stability characteristics. In the present work we investigate the optical band gap of the Cl16FePc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…According to DFT calculations, the HOMO and LUMO energy levels of CuPcCl x decrease in comparison with unsubstituted CuPc derivatives [26,27]. Koshy et al [28] investigated the effect of annealing temperature on the optical band gap of FePcCl 16 films, and considered their possible applications as active layers of molecular electronic devices. Anchar et al [29] have shown that the conductivity of CuPcCl 4 pellets is about four orders of magnitude higher than that of unsubstituted CuPc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to DFT calculations, the HOMO and LUMO energy levels of CuPcCl x decrease in comparison with unsubstituted CuPc derivatives [26,27]. Koshy et al [28] investigated the effect of annealing temperature on the optical band gap of FePcCl 16 films, and considered their possible applications as active layers of molecular electronic devices. Anchar et al [29] have shown that the conductivity of CuPcCl 4 pellets is about four orders of magnitude higher than that of unsubstituted CuPc.…”
Section: Introductionmentioning
confidence: 99%
“…Ling, Bao and Erk determined that the carrier mobility of a CuPcCl 16 film deposited at an elevated substrate temperature in air-stable n-channel transistors was 10 −2 cm 2 V −1 s −1 [30]. It is known that the electrical properties of phthalocyanines and other molecular crystals are dependent upon the phase composition, morphology and orientation of molecules in thin films [6,7,28]. It is worth mentioning that in most of the abovementioned articles, the structure of thin films MPcCl x was not studied.…”
Section: Introductionmentioning
confidence: 99%
“…E.g., chlorine substitution in MPc was shown to modify solubility, conductivity, nonlinear optical and photochemical properties of MPc films [12,13]. In a recent work, the authors [14] studied the annealing temperature dependence of the optical band gap of the FePcCl 16 thin films and considered possible applications of the latter as components of molecular electronic devices. Furthermore, the array of rectangular microtubes of CuPcCl 16 with a large interior width of 1.4 -1.8 μm and thin walls (80 -100 nm) was synthesized and characterized by means of scanning and transmission electron 4 microscopies, XRD, FTIR, and X-ray photoelectron spectroscopy [15].…”
Section: Introductionmentioning
confidence: 99%
“…19,[22][23][24][25] Halogenated phthalocyanines, such as F 16 CuPc and Cl l6 CuPc, act as n-type semiconductors. 13,[26][27][28] In halogenation, fluorination strongly affects the energy level because of the strong electron-withdrawing ability of fluorine atoms. Murdey et al have measured the HOMO and LUMO energy levels of CuPc, an isomer of F 8 CuPc, and F 16 CuPc from the results of ultraviolet photoemission and inverse photoemission spectroscopy.…”
Section: Introductionmentioning
confidence: 99%